Penerapan Kewenangan POLRI Melakukan Penegakan Hukum Terhadap Pelaku Pidana Penambangan Batu Bara Illegal - Fahrurrozi, Fahrurrozi; Said, Yusuf Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Indonesia is a country rich in minerals (mining). The minerals contained in the form of gold, silver, copper, oil and natural gas, coal and many other natural potentials that can support the development of the country. All mining materials are controlled by the state and used for the entire Indonesian nation, based on the fifth principle of Pancasila as a unified whole, the existence of norms or rules in the provisions of Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia. “Earth, water and natural resources contained therein shall be controlled by the State and used for the greatest prosperity of the people.